Hubungan Pola Asuh Orang Tua dengan Pembentukan Kepribadian pada Siswa SMA Argopuro Panti Kabupaten Jember - Aini, Nur; Dewi, Erti Ikhtiarini; Fitria, Yeni (UPT Percetakan dan Penerbitan Universitas Jember, 2024)
In the adolescent phase, individuals will experience the process of searching for self-identity related to personality formation in adolescents. One of the factors that influence personality formation in adolescents is the application of parenting styles. This study analyzes the relationship between parenting style and personality construction in SMA Argopuro Panti, Jember Regency students. This study used a correlational research method with a cross-sectional approach. The sampling technique was Stratified Random Sampling with a total sample of 151 students. Data collection uses the Parental Authority Questionnaire (PAQ) and Big Five Personality questionnaires. The results showed that the majority received authoritarian parenting parents, namely as many as 86 respondents (57%), and extraversion personalities, as many as 89 respondents (58.9%). The results of the bivariate test with Cramer's V showed that the p-value = 0.000 <0.05 with a correlation coefficient of 0.355. This means a relationship exists between parenting style and the personality formation of SMA Argopuro Panti Jember Regency students. Nurses' role is essential to educate parents and adolescents about parenting styles and adolescent personality.